Os programas de ações afirmativas em prol da população transexual e travesti - Pierini Neto, Edgar (2019)
The history of human sexuality was characterized by the exclusion and discrimination of bodies considered abject by prevailing social standards. At present, this situation can still be verified with regard to sexual minorities, among whom transvestites and transsexuals suffer from high levels of prejudice and stigmatization. In this field, it is important to emphasize the importance of queer theory and studies aimed at this population, which, by producing a theoretical framework directed to the protection of transgender people, allowed small advances respect for the dignity of the human person of such individuals. When analyzing transsexuality and transvestitism from the standpoint of fundamental rights and the Federal Constitution, it is clear the need to promote affirmative actions in favor of the mentioned sexual minority with the scope of reducing existing inequalities, promoting diversity and inclusion of this group in social and political spaces. Positive discriminations in favor of minorities is aimed at achieving material and pluralistic equality, and in this sense, when observing constitutional values and proportionality, their consonance with the Democratic Rule of Law is evident. Thus, the drastic degree of social exclusion to which the transgender population is subjected points to a deficient protection of this public, which corroborates the constitutional duty in the institution of affirmative actions in the most diverse fields to transsexuals and transvestites. Nowadays, there are some initiatives with this purpose that have good results. However, their reach is still small, so there is a need to expand existing policies and establish new initiatives that promote and protect the basic rights of the population in question